Formulasi Strategi Bisnis untuk Pengiriman Ekspor Udara - Charles AN; Galih Maulana; Wynd Rizaldi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
PT Logwin Air and Ocean Indonesia is in 10th position out of the top 10 forwarding companies that export air cargo, with a market share of 3.22% in 2017. The biggest strength of PT Logwin Air and Ocean Indonesia is having the resources / man power that knowledgeable and reliable. While the lack of shipment nominations (shipment nominations) is the strongest weakness for PT Logwin Air And Ocean Indonesia. The biggest opportunity for PT Logwin Air and Ocean Indonesia is the Indonesian government's policy to increase exports. The biggest threat faced by PT Logwin Air And Ocean Indonesia is price competition with competitors. Based on the CPM Matrix, the company’s rank is in the 5th position after DHL, Schenker, Yusen and Panalpina. In IE Matrix, the company is in cell V that is hold and maintain with a total score of internal strategy factors (2.31) and total external strategy score of (2.36). Based on the 4-K SWOT analysis and Grand Strategy Matrix, it is known that the horizontal axis (X) is (1.45) and the vertical axis (Y) is (0.48), so the company's position is illustrated in quadrant I. There are two alternative strategies obtained from the results of the IE, SWOT 4K, BCG and Grand Strategy matrix analysis, namely: Market Penetration and Product Development, and in the QSPM Matrix, Market Penetration strategies are obtained with a total attractiveness value of (5 , 52) as the first priority and followed by a Product Development strategy (Product Development) with a total attractiveness value of (5.44).